Complementary feeding practices and determinants of micronutrient status of rural young children in the Philippines - Goyena, Eva A.; Maniego, Ma. Lynell V.; Ducay, Apple Joy D.; Tandang, Nancy A.; Talavera, Ma. Theresa M.; Barba, Corazon VC (2019)
Owing to suboptimum feeding practices, Filipino infants are vulnerable to undernutrition during the first two years of life. This present paper aimed to determine the complementary feeding practices of young children 6?23 mo old, and to assess the micronutrient status of children ? with particular reference to hemoglobin (Hb), ferritin, zinc, and their determinants. The present paper was part of the randomized community trial (RCT) on micronutrient powder (MNP) supplementation involving four randomly selected barangays in Calauan, Laguna, Philippines, and covering a total of 126 children 6?23 mo old. Baseline and endline assessments were done to determine Hb, ferritin, retinol, zinc, and C-reactive protein (CRP) levels. Child?s breastfeeding and complementary feeding practices, weight, length, and dietary intakes were collected monthly for six months. Stepwise linear regression was performed to determine the biological and environmental factors associated with micronutrient status of the study children. The 24-hour dietary assessment showed that children consumed mainly thin porridge or lugaw ? boiled rice mixed with broth of boiled fish, meat, or vegetables ? and biscuits/bread as complementary foods. The majority of children had inadequate intake of energy, protein, and key micronutrients based on a single day food recall at endline assessment. Carbohydrates from complementary food remained the major energy contributor among children 6?11 mo (68.0%) and 12?23 mo old (66.9%). The prevalence of stunting, underweight, and wasting was 10.4%, 13.6%, and 8.0%, respectively. The mean Hb was 11.2 g/dL, of which 35.7% of infants were anemic (Hb<11.0 g/dL). The mean serum ferritin used to indicate storage iron was 23.8 ug/L, of which 27.8% of infants had low iron storage. Hb, ferritin, and zinc concentrations at endline consistently related to the corresponding outcome variables of Hb, ferritin, and zinc at endline, respectively. Adequacy of energy, vitamin A, and iron intake was positively associated with Hb at endline period. Other nutrition factors played a role in the level of Hb, including continued breastfeeding beyond one year and episode of diarrhea. Ferritin level at endline was associated with vitamin C adequacy, breastfeeding practices, child?s length, marker of infection (CRP), and occupation of household head in the expected directions. Stunting was strongly associated with zinc concentration at endline. There is an urgent need to improve the complementary food in terms of energy, protein, and micronutrient adequacy of complementary foods of children in the studied communities through increasing density and bioavailability of macro - and micronutrients. (Author's abstract)